Restoring the Spirit of Stewardship: AbdulHamid AbuSulayman’s Educational Reform Project - Al-Samadi, Khaled (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2023)
This study aims to extrapolate the major orientations of AbdulHamid AbuSulayman’s educational thought. It focuses on AbuSulayman’s educational reform project, examining its founding reference, its objectives, its intellectual contents, and its practical application, and how these cohere to diagnose the intellectual and educational defects preventing the Ummah from regaining the spirit of initiative and stewardship. The study offers a critical analysis of AbuSulayman’s educational reform methodology in light of other approaches that seek to address the Ummah’s challenges. The study’s main objective is to capture a practical framework in which AbuSulayman’s educational reform project can treat the issues impeding the Ummah's ability to restore its civilizational prestige.